Online Single Submission For Cyber Defense and Security in Indonesia - Inggarwati, Melodia Puji; Celia, Olivia; Arthanti, Berliana Dwi (Universitas Negeri Semarang, 2020)
National defense and security are important issues to face the Industrial Revolution 4.0. It is undeniable that Indonesia's defense and security system's weaknesses lead to many cybercrimes. In the business licensing's sector, the Online Single Submission's (OSS) mechanism known as an important role in increasing the ease of doing business in Indonesia. The existence of the OSS system which contains a lot of important data from stakeholders that make it requires security and guarantees. But in reality, the existing OSS digital licensing system hasn't able to optimize the implementation of cyber's defense and security in Indonesia. Therefore, a breakthrough is needed to make the OSS system more perfect by integrating and guaranteeing the data through the establishment of minimum safety standards. This normative-juridical research uses secondary data that processed through literature studies and analyzed qualitatively.